Metal nanocluster‐based devices: Challenges and opportunities - Lizhen Chen; Andres Black; Wolfgang J. Parak; Christian Klinke; Indranath Chakraborty (Aggregate, 2022)
Abstract Atomically precise nanoclusters (NCs) with fascinating physicochemical characteristics different from their nanoparticles (NPs) counterparts have gained increasing attention in diverse fields of applications. The foremost outcome of such NC‐based applications is leading to transform them into devices. In fact, there are already some reports on the development of NC‐based devices. For instance, NCs exhibit their potential in solar cells, showing high light‐harvesting efficiency comparable to traditional semiconductor solar cells. Further, recent progress in characterizing Au NCs films and micro‐crystals shows semiconductor‐like properties such as field effect and photoresponse. These successes indicate that metal NCs possess a high potential for application in multidisciplinary areas for advancing the development in fundamental and practical purposes. However, no such comprehensive review is available to highlight recent advances and new applicable devices based on noble metal NCs. Herein, we reviewed the recent development in this area, including synthesis challenges of metal NCs and related applications of NC‐sensitized solar cells, strain sensors, chemo‐/biosensors, transistors, floating memory, and other devices. Furthermore, the future opportunities such as modifying synthetic methods to make other metal NCs, enhancing the efficiency of solar cells, and exploring more NC‐based devices alternative to semiconductors are pointed out. We hope that rapidly increasing interest in NC‐based devices will stimulate the research in this area and inspire the advances in combined devices accordingly.